THE EVALUATION OF YIELD AND AGRONOMIC TRAITS OF FLAX GENOTYPES UNDER LATVIAN CONDITIONS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
This study aim was evaluated of flax genotypes regarding productivity, resistance to lodging and diseases as well as yield dependence relationships among phenotypic and quality traits. The 14 fibre flax genotypes were evaluated in field conditions on the background of natural infection from 2014 to 2018 for agronomically important traits and from 2015 to 2018 for occurrence diseases of flax. The data were recorded for the 15 following agronomic traits, such days to flowering, days to early yellow ripening stage, total plant height, technical height, stem yield, fibre content, 1000 seed weight, vessels per plant, harvest index, seed yield, oil content, resistance to lodging and fungal diseases during early yellow ripening stage. Genotypic and phenotypic correlations between yield and yield components were identified that total plant height, technical height and days to early yellow ripening stage played a major role on stem yield as well vessels per plant and harvest index on seed yield. The flax genotypes ‘Vilani’, ‘L26-1’, ‘K9-1’, ‘T36-1’, ‘S37-1’ exhibited significant highest stem yield ranging from 643.20 to 693.32 g m-2 and technical length ranging from 65.90 to 70.58 cm comparing to standard variety ‘Vega 2’. The most perspective genotype of ‘Vilani’ with quit low susceptibility to anthracnose, pasmo and powdery mildew and resistance to lodging was identified.